Intergenerational Transmission of Resilience? Sense of Coherence Is Associated between Lithuanian Survivors of Political Violence and Their Adult Offspring - Kazlauskas, Evaldas; Gailiene, Danute; Vaskeliene, Ieva; Skeryte-Kazlauskiene, Monika (Frontiers in Psychology, 2017)
Little is known about intergeneration effects on mental health in the families of survivors of political oppression of communist regime in Central and Eastern Europe. We aimed to explore posttraumatic stress in the second generation of the Lithuanian survivors of political violence, and analyze links between parental and adult offsprings’ sense of coherence in the families exposed to political violence during the oppressive communist regime in Lithuania. A total of 110 matched pairs of communist regime political violence survivors (mean age = 73.22 years) and their adult offspring (mean age = 44.65 years) participated in this study. Life-time traumatic experiences and sense of coherence were measured in both parents and their offspring. Posttraumatic stress symptoms were assessed in the second generation of survivors. We found a high vulnerability in the second generation of the Lithuanian families of political violence survivors, with a 29% of probable PTSD in the second generation based on self-report measures. A significant positive correlation between parental and adult offsprings’ sense of coherence was found. Posttraumatic stress symptoms were associated negatively with a sense of coherence in the second generation. Our study indicates the links between parental and the second generation’s sense of coherence in the families of survivors of political violence. The study raises broader questions about the intergenerational aspects of resilience. Further studies are needed to explore the links between parental and child sense of coherence in other samples.